MEASURING PT. AEI EMPLOYEE PERFORMANCE : IN TERMS OF OCCUPATIONAL HEALTH AND SAFETY (K3) AND COMPETENCY - susanto (FEB - Universitas Lampung, 2024)
This research aims to analyze the influence of occupational health and safety (K3) on employee performance at PT. AEI South Jakarta, to analyze the influence of competency on employee performance at PT. AEI South Jakarta, to analyze the influence of occupational health and safety (K3) and competency together on employee performance at PT. AEI South Jakarta. Analysis in the research uses SEM PLS, where Structural Equation Modeling (SEM) is structural equation modeling in the form of a set of statistical methods based on measurements and structural models. The sample in this research is employees at PT. AEI South Jakarta as many as 126 employees will be used as respondents to fill out the questionnaire using the Slovin sampling technique. The research results state that K3 has a significant positive effect on employee performance, competency has a significant positive effect on employee performance, K3 and competency together have a significant effect on employee performance. K3 and competency contribute to employee performance by 77.6%.